2015
DOI: 10.1021/acs.jpclett.5b00078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Design Principle behind Optimal Sizes of Photosynthetic LH2 Complex: Taming Disorder through Cooperation of Hydrogen Bonding and Quantum Delocalization

Abstract: The light harvesting 2 (LH2) antenna complex from purple photosynthetic bacteria is an efficient natural excitation energy carrier with well-known symmetric structure, but the molecular level design principle governing its structure-function relationship is unknown. Our all-atomistic simulations of nonnatural analogues of LH2 as well as those of a natural LH2 suggest that nonnatural sizes of LH2-like complexes could be built. However, stable and consistent hydrogen bonding (HB) between bacteriochlorophyll and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 40 publications
6
43
0
Order By: Relevance
“…The most important residues contributing to the solvatochromic shift of α-BChl are the hydrogen-bonding residue (Trp(W)45 in B800-850 and Tyr(Y)41 in B800-820), and the close residues of the neighboring β-apoprotein, Ala(A)29 and His(H)30 for both complexes [39,40,41]. However, also the neighboring β-BChl on the same unit has a non-negligible contribution.…”
Section: Qy Site Energiesmentioning
confidence: 99%
“…The most important residues contributing to the solvatochromic shift of α-BChl are the hydrogen-bonding residue (Trp(W)45 in B800-850 and Tyr(Y)41 in B800-820), and the close residues of the neighboring β-apoprotein, Ala(A)29 and His(H)30 for both complexes [39,40,41]. However, also the neighboring β-BChl on the same unit has a non-negligible contribution.…”
Section: Qy Site Energiesmentioning
confidence: 99%
“…Strümpfer and K. Schulten, 2012). Application of the GME-MED approach (Jang et al, 2014(Jang et al, , 2015 showed that the rate can change significantly depending on the realization of the disorder and the inter-LH2 distances that are consistent with AFM images. Figure 15 shows the distribution of rates at 300 K between two LH2 complexes separated by a center-tocenter distance of 7.5 nm.…”
Section: Lh2 Complexmentioning
confidence: 87%
“…The outcomes of these calculations, in combination with empirical correction factors to complement numerical errors, laid the foundation for many exciton models that followed. In addition, already in 2002, all atomistic MD simulation of LH2 complex was shown to be feasible (Damjanović et al, 2002), providing the basis for more recent advances (Cupellini et al, 2016;Jang et al, 2015;Montemayor et al, 2018;Olbrich and Kleinekathöfer, 2010;Sisto et al, 2017). In this section, some of the outcomes of these recent computational studies for the LH2 antenna complex of Rps.…”
Section: Lh2mentioning
confidence: 98%
See 2 more Smart Citations